THE POTRAYAL OF KING ARTHUR IN VIDEO GAMES FROM TRANSSTYLIZATION PERSPECTIVES: AN INTERTEXTUAL STUDY - Evita (CrossOver Journal of Adaptation Studies, 2022)
Transstylization is a stylistic rewriting, a transposition whose main function is a change of style. It is concerned with the preparation of a text. A stylistic rewriting of a text can be applied by stylization or destylization. This research attempts to reveal what transstylization techniques are applied to the portrayal of King Arthur in video games, adapted from the book King Arthur Myth-Making and History, and how the transstylization generates losses and gains in the characterization of King Arthur. This study uses a qualitative method that allows the researcher to collect, analyze, and draw conclusions from the data, which are in the form of visualization, characteristics, names, and stories that are in accordance with the book. The data in this study were analyzed using Spradley’s technique of analysis. Transstylization by Gerard Genette and adaptation theory by Linda Hutcheon were applied to answer the problem in this research. From the seventy-six data found, it can be concluded that destylization is the dominant technique of transstylization applied to the portrayal of King Arthur in video games. This shows that the visualization, name, and story of King Arthur in this research have a different pattern from the book. This research also shows how transstylization causes losses and gains in the characterization of King Arthur in video games through Telling-Interacting. These findings enrich the knowledge about the transstylization of King Arthur from the book King Arthur Myth-Making and the history of video games.